PRAKTIK PENGUTIPAN JASA PENITIPAN GADAI EMAS DI PT. PEGADAIAN SYARIAH KOTA SIGLI - Hamdiyah (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2020)
This scientific paper discusses "The Practice of Citing Gold PawnDeposit Services at PT. Syari'ah Pegadaian City of Sigli. "In this study there aretwo problems, namely: the process of citing day care services and thedetermination of day care services in the practice of gold pawning at PT. PegliianSyariah City of Sigli. The research uses several methods, namely field research(Field Research), with observation techniques, interviews, and documentation,and Library Research (Library Research). The results of the study explained thatthe process of quoting gold deposit services is carried out based on the provisionsset by the Islamic Pegadaian with maintenance costs / gold deposit servicescalculated per 10 days with a maturity of 120 days (4 months) with the value forujrah (day care fees), namely 0.7% of the estimated gold. If it cannot pay off whendue, then it can be extended by paying the deposit fee (rent place) only. This is inaccordance with the Islamic legal basis based on the National Sharia CouncilFatwa Number: 25 / DSN-MUI / III / 2002 concerning rahn which states thatloans by mortgaging goods as collateral for debt in the form of rahn are allowed,and DSN Fatwa Number: 26 / DSN-MUI / III / 2002 concerning gold rahn, andDSN Fatwa Number: 09 / DSN-MUI / IV / 2000 stating that the storage of goods(marhun) is based on an ijarah agreement.